Foreign Direct Investment, Trade Dynamics, and Economic Growth in Indonesia: Evidence from a Vector Error Correction Model - Renaldi, Renaldi; Aprilia, Riska; Qodri, Lutfi Asnan (Journal of Regional Economics Indonesia, 2025)
This study examines the short-run dynamics and long-run relationships between foreign direct investment (FDI), exports, imports, and economic growth in Indonesia using annual time-series data from 1990 to 2024. Employing a Vector Error Correction Model (VECM), the analysis captures both long-term equilibrium relationships and short-term adjustments among the variables. The results reveal the existence of cointegration, indicating a stable long-run relationship. Empirical findings show that, in the long run, FDI has a statistically significant negative effect on economic growth, while imports exert a positive and significant impact. Exports, however, do not demonstrate a significant effect on growth in either the short or long run. These results suggest that FDI inflows in Indonesia are largely concentrated in non-productive sectors, limiting their contribution to sustainable economic growth, whereas imports play a crucial role in supporting industrial production through capital goods and intermediate inputs. The study highlights the importance of redirecting FDI toward high-value-added sectors and maintaining strategic import policies to promote long-term economic growth.